(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: Inappropriate starting of complementary feeding is an important factor leading to infant growth delay and malnutrition. This study was aimed to determine the complementary feeding pattern and some related factors in health care centers in Khorramabad. Methods: This cross-sectional study, included 300 one year old infants who had referred to nine health care centers in Khorramabad by multistage sampling. In present study, we used a questionnaire included individual information about mothers and infants and a checklist for evaluating breastfeeding and complementary feeding. Chi-square test and one way ANOVA were used to analyze the data. Results: In present study, 50.7% of infants were girls and 60.3% of cases were the first infant in their family. 59.3% of infants were delivered by cesarean. Average age of starting complementary feeding was 0.5 8.5. 75.7% of infants had exclusive breastfeeding up to first six months of their life. Among most cases, the first complementary food was rice flour porridge (29.3%) and almond porridge (15.7%). Most mothers had acquired necessary information about complementary feeding by using booklets (20.7%) and physician guidance (16.7%). There was a statistically significant relationship between age of starting complementary feeding and mother’s education (P=0.043) level and employment status (P=0.001). Conclusion: Related authorities should begin comprehensive and effective education by using novel training strategies to raise mothers’ knowledge about age of starting complementary feeding and how to do it at health care centers.